Contentment: Perceived Completeness across Cultures and Traditions. Issue 3 (September 2016) - Cordaro, Daniel T.; Brackett, Marc; Glass, Lauren; Anderson, Craig L.
Over the past 2 decades, a major focus in psychological research has been on pursuing happiness, positivity, and optimal human flourishing. Interestingly, little attention has been paid to contentment, which, according to over 4, 000 years of spiritual, philosophical, and theoretical discourse, is an emotion that sits at the deepest core of human wellbeing and is foundational to the experience of fulfillment in life. This article synthesizes etymological, religious, philosophical, and psychological treatments of contentment from multiple languages and traditions. Derived from these perspectives, it also presents a prototype approach to contentment, its core affect features and cross-cultural variations. Finally, it presents theory-grounded hypotheses intended to initiate future research on the topic. We propose a primary appraisal theme that is at the root of all experiences of contentment: perceived completeness, which refers to the perception that the present situation is enough and entire.